The Effects of Resistant Starch Consumption in Adult Patients With Chronic Kidney Disease: A Systematic Review. (July 2022) - Kingra, Kulwant; Curtis, Sarah; Mollard, Rebecca C.; Shamloo, Maryam; Askin, Nicole; Tangri, Navdeep; MacKay, Dylan
Background: Resistant starches (RSs) are not digested by human digestive enzymes and pass through the upper digestive tract to become substrates for colonic bacteria. Resistant starch supplementation has shown promising results in altering the microbiota of animal models of chronic kidney disease (CKD). Resistant starch consumption may influence the production of uremic toxins in CKD. Objective: To conduct a systematic review to determine whether the consumption of RS reduces the progression of kidney disease in adult patients with CKD. Design: We included randomized controlled trials comparing RS supplementation to placebo, no treatment, or standard care. Cochrane Central, Embase, MEDLINE, Web of Science, and CINAHL databases were searched. There was no limitation on publication date, but only English manuscripts were included. The search was conducted in July 2020. Patients: Adult outpatient populations with CKD, using any recognized diagnostic criteria. Measurements: The primary outcome was change in glomerular filtration rate (GFR) from baseline through the end of the trial in patients not on dialysis; secondary outcomes included change in uremic toxin concentrations (p-cresol/p-cresyl sulfate [p-CS], indoxyl sulfate [IS]) and inflammatory markers (tumor necrosis factor alpha [TNF-α], C-reactive protein [CRP], interleukin 6 [IL-6]) from baseline through the end of the trial, and changes in self-reported symptom scores. Methods: The Cochrane Collaboration Risk of Bias tool was used to assess risk of bias in included studies. The systematic review results are reported following the Preferred Reporting Items for Systematic Reviews and Meta-Analysis guidelines. Results: We identified 4 unique studies, reported in 9 publications that met our inclusion criteria, including a total of 215 enrolled participants. Results were calculated using data from the longest reported follow-up time. The primary outcome of changes in kidney function markers was only studied in 1 trial; this trial reported an increase in creatinine and a decrease in blood urea nitrogen; no changes in GFR were reported. A review of the secondary outcomes showed an overall decline in IS, TNF-α, and IL-6, in RS groups, but with mixed results in p-CS and CRP/high-sensitivity CRP. Safety data showed that RS was well tolerated with no reports of excessive side effects. Limitations: We determined a meta-analysis was not feasible due to clinical heterogeneity between study populations and differences in reported outcomes in the included studies. Conclusion: There is limited and inconsistent evidence on the impact of RS in adult patients with CKD. Further research is needed to determine the safety and efficacy of RS supplementation in this population.